2008
DOI: 10.1016/j.jrp.2007.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The worker scale: Developing a measure to explain gender differences in behavioral self-handicapping

Abstract: Research has consistently found that men engage in more behavioral self-handicapping than do women. We first review evidence suggesting that these gender differences result from women placing more importance on displaying effort than do men. We then present the results of two studies seeking to develop measures of beliefs about effort that might explain these gender differences in behavioral self-handicapping. Women, across a wide range of measures, placed more importance on effort than did men. However, only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 48 publications
2
57
0
6
Order By: Relevance
“…Generally, the use of self-handicapping strategies is associated with low self-esteem, reports of psychological symptoms (such as stress and anxiety), poor academic performance and lack of organization and academic goals (Hendrix & Hirt, 2009;Martin et al, 2001;McCrea, 2008;Schwinger & Stiensmeier-Pelster, 2011). Regarding the differences between genders, the data indicate that women evaluate self-handicapping behaviors more negatively than men and use these strategies less often (Hirt et al, 2003;Hirt, McCrea, & Kimble, 2000;McCrea et al, 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, the use of self-handicapping strategies is associated with low self-esteem, reports of psychological symptoms (such as stress and anxiety), poor academic performance and lack of organization and academic goals (Hendrix & Hirt, 2009;Martin et al, 2001;McCrea, 2008;Schwinger & Stiensmeier-Pelster, 2011). Regarding the differences between genders, the data indicate that women evaluate self-handicapping behaviors more negatively than men and use these strategies less often (Hirt et al, 2003;Hirt, McCrea, & Kimble, 2000;McCrea et al, 2008).…”
mentioning
confidence: 99%
“…Self-handicapping strategies can be used in many contexts, such as management, sports and in academia. The frequent use of these strategies jeopardizes performance and interferes with success (Finez & Sherman, 2012;McCrea, Hirt, Hendrix, Milner, & Steele, 2008;Smith, Hardy, & Arkin, 2009). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of Study 1 was to explicate the relationship between selfhandicapping (Jones & Rhodewalt, 1982) and free will beliefs (Rakos, Laurene, Skala, & Slane, 2008;Paulhus & Carey, 2011;Deery, Davis, & Carey, 2015), as well as related constructs such as beliefs about control (Levenson, 1973;Lefcourt, von Baeyer, Ware, & Cox, 1979), and effort (Schwarzer Bäßler, Kwiatek, Schröder, & Zhang, 1997;McCrea, Hirt, Hendrix, & Milner, 2008). We expected that there would be a positive relationship between free will beliefs, internal locus of control, self-efficacy, and belief in the value of effort, as well as a negative relationship between these constructs and scores on the selfhandicapping scale.…”
Section: Studymentioning
confidence: 99%
“…McCrea, Hirt, Hendrix, Milner, and Steele (2008) developed The Worker Scale in an effort to explain gender differences in behavioral self-handicapping. Across a variety of effort based belief measures, McCrea et al found that women place a higher value than men on effort, perceive effort as normative, view effort rather than ability as more important in others, and enjoy putting forth more effort.…”
Section: Gender and Self-handicappingmentioning
confidence: 99%